ANALISIS KEANEKARAGAMAN JENIS TUMBUHAN OBAT TRADISIONAL BERKASIAT UNTUK PENGOBATAN PENYAKIT SALURAN KENCING DI KECAMATAN KINTAMANI, KABUPATEN BANGLI PROVINSI BALI - Ni Nyoman Darsini (Bumi Lestari Journal of Environment, 2013)
AbstractThe research has done on medicinal plants are believed to cure or treat urinary tractdisorders in 15 villages of Kintamani district Bangli. Based on the results of researchthrough the interview process with the public, traders and some interviewees ceraken JeroBalian it is known there are 47 types of plants are believed to overcome the disease urinarytract disorders. Various kinds of urinary tract disorders can be cured by 47 different herbsare-different. Of the 47 plant species are classified as rare plants, three plants namely: pule(Astolnia scholaris), purnajiwa (Euchresta horsfieldii (Lesch) Benn), and suren (Taonasuroni Merr). The dominant plant organ used as medicine are the leaves (59.57%).